2021
DOI: 10.1590/1980-0037.2021v23e76402
|View full text |Cite
|
Sign up to set email alerts
|

Assessment methods of vastus lateralis muscle architecture using panoramic ultrasound: a new approach, test-retest reliability and measurement error

Abstract: Extended-field-of-view ultrasonography is a valid alternative to determine the dimensions of the skeletal striated muscle; however, some factors may influence the final measurement. The aim of this study was to determine the test-retest reliability and measurement error of vastus lateralis muscle architecture variables through internal anatomical landmarks and to compare three fixed determined points using extended-field-of-view ultrasonography. Twelve young (24 ± 6 years) adult university male students partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In a recent study carried out by our laboratory, it was observed that measurements performed on different days have high consistency (ICC MT = 0.964; ICC FL = 0.947; ICC FA = 0.942), low absolute error (TEM MT = 0.07 cm; TEM FL = 0.31 cm; TEM FA = = 0.92º), and low variability between measurements (CV MT = 2.9%; CV FL = 2.9%; CV FA = 4.1%) [21]. Thus, it is possible to attribute a greater power of certainty to the results of the comparison between the FL obtained by the panoramic US and estimated by equations 1 and 2 that used the variables MT, FA, and the FL itself for the prediction calculation.…”
Section: Reliability and Measurement Errormentioning
confidence: 89%
“…In a recent study carried out by our laboratory, it was observed that measurements performed on different days have high consistency (ICC MT = 0.964; ICC FL = 0.947; ICC FA = 0.942), low absolute error (TEM MT = 0.07 cm; TEM FL = 0.31 cm; TEM FA = = 0.92º), and low variability between measurements (CV MT = 2.9%; CV FL = 2.9%; CV FA = 4.1%) [21]. Thus, it is possible to attribute a greater power of certainty to the results of the comparison between the FL obtained by the panoramic US and estimated by equations 1 and 2 that used the variables MT, FA, and the FL itself for the prediction calculation.…”
Section: Reliability and Measurement Errormentioning
confidence: 89%
“…Of the 26 studies included, 4 were validity studies [18][19][20][21] , and 4 were reliability only [22][23][24][25] . Eighteen were of reliability and measurement error [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . Four hundred ninety subjects were included, from which 311 men, 164 women, and 15 were not identified.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Our laboratory experience indicates that the methodological care of the entire process, associated with the constant training of the raters, has decreased TEM. In the first study, our group presented an intra-rater TEM of 0.07 cm for vastus lateralis MT 43 . In a recent study, intra-and inter-rater TEM decreased to 0.01 to 0.03 cm for the same variable 26 .…”
Section: Quality Of Muscle Thickness Measurement By Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation